Geomorphology of Karlıova Basins And Its Environment (Bingöl) - Avci, Vedat; Günek, Halil (Fırat University, 2022)
In this study, the general geomorphology of Karlıova Basin and its surroundings has been evaluated, morphometric indices have been applied to the sub-basins that were determined in the fault zones, and lineament analysis has been done. Karlıova Basin, which is located at the eastern most point of the Anatolian Plate, has an important place in the neotectonics of our country. The basin corresponds to the area called the Karlıova triple-junction, where North Anatolian Fault (NAF), East Anatolian Fault (EAF) and Varto Fault intersect. The basin developed as a fault-wedge basin depending on the movement of the NAF and the EAF in different directions, was opened to external drainage as a result of backward erosion of Göynük Stream in the Quaternary. In the neotectonic period, with the increase of vertical tectonic movements, mountainous areas along the EAFZ in the south, Bahçeköy and Tokluklar Faults in the west took their current positions. The main geomorphological units were formed by mass uplift and fault tectonics in this period. Landforms of tectonic geomorphology in and around the basin and terraces in the river valleys indicate periodic uplift. According to quantitative analyses, the lineaments are centered on NE-SW and NW-SE directions. These are in line with the direction of the NAF and the EAF. The indices analyses show that the effect of the NAF and Bahçeköy Fault on the morphology is higher than that of the EAF in the basin.

Bu çalışmada Karlıova Havzası ve çevresinin genel jeomorfolojisi değerlendirilmiş, fay zonlarında belirlenen alt havzalara morfometrik indisler uygulanmış ve çizgisellik analizi yapılmıştır. Anadolu Levhası’nın en doğu ucunda yer alan Karlıova Havzası, ülkemizin neotektoniğinde önemli bir yere sahiptir. Havza, Kuzey Anadolu Fayı (KAF), Doğu Anadolu Fayı (DAF) ve Varto Fayı’nın kesiştiği ve Karlıova üçlü eklemi olarak adlandırılan alana karşılık gelmektedir. KAF ve DAF’ın farklı doğrultuda hareketine bağlı olarak fay kaması havzası şeklinde gelişen havza, Kuvaterner’de Göynük Çayı’nın geriye aşındırması sonucunda dış drenaja açılmıştır. Neotektonik dönemde dikey yöndeki tektonik hareketlerin de ağırlık kazanmasıyla, güneyde DAFZ, batıda Bahçeköy ve Toklular Fayları boyunca dağlık alanlar yükselerek bugünkü konumlarını almıştır. Bu dönemde yaşanan toptan yükselmeler ve fay tektoniği altında ana jeomorfolojik birimler oluşmuştur. Havza ve çevresinde tektonik jeomorfolojiye ait yer şekilleri ile akarsu vadilerindeki taraçalar dönemsel yükselmeleri göstermektedir. Sayısal analizlere göre çizgisellikler, KD-GB ve KB-GD doğrultusunda yoğunlaşmaktadır. Bu doğrultular, KAF ve DAF’ın doğrultusu ile uyumludur. İndis analizleri havzada KAF ve Bahçeköy Fayı’nın morfolojideki etkisinin DAF’a göre daha yüksek olduğunu ortaya koymaktadır.
KARLIOVA HAVZASI VE ÇEVRESİNİN (BİNGÖL) JEOMORFOLOJİSİ